ANALISIS SYAIR “ HATI PEREMPUAN ADALAH BATU-BATU “ KARYA ABBAS BIN AHNAF : KAJIAN ILMU MA’ANI - mutmainnah, mutmainnah; Wahyuni, Sri (Institut Kariman Wirayudha Sumenep, 2024)
This research is related to the analysis of a poem entitled